Genetic and cropping system effects on yield and postharvest characteristics of Musa species in Southeastern Nigeria - Baiyeri, K.; Tenkouano, A.; Mbah, B.; Mbagwu, J. (1999)
Post-harvest characteristics of 36 Musa genotypes were evaluated under two cropping systems. Genotypes included AAA x AA, AAB x AA and ABB x AA (or BB) and their landraces AAA, AAB and ABB grown under monocropping and in the alleys of natural multi-species hedgerows. Significant differences (P < 0.01) were found among genomic groups for bunch and fruit weights, pulp yield, dry matter content, pulp firmness, shelf-life, and market potential index. Cropping systems were also significant for all traits except for pulp firmness and shelf-life. Significant interactions between genotypes and cropping systems were found for all traits except dry matter content and pulp firmness. Tetraploid hybrids had lower pulp firmness but higher shelf-life and market potential index than the triploid genotypes. Among the triploid landraces, AAA genotypes had longer shelf-life but expressed the lowest market potential index due to their lower pulp yield and dry matter content. The AAB x AA hybrids consistently expressed higher pulp firmness, shelf-life and market potential index than other tetraploid hybrids. The alley-cropping system resulted in higher values for most post-harvest characteristics than the monocropping system.